Themes of Gender and Identity in Mahashweta Devis Fiction: Exploring Gender and Identity in Mahashweta Devi's Fiction (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Writing mirrors life. It happens in the midst of the trap of sociocultural relationship. It takes its introduction to the world in the midst of the general public. The two people have added to the field of experimental writing and writing. Ladies have made a surprising commitment to the fiction in Indian English Literature. Among the multitudinous new participants to the universe of Indian English Women composing. Mahashweta Devi is acclaimed by both Bengali (provincialnearby) and public who have acces to her work through interpretation. This access has made her a commonly recognized name over basically the whole subcontinent. She is one of those uncommon authors who consistently seek to discover and investigate something testing and new, and never acknowledge the current goals. As an imaginative author, he commitment is significant, both in importance and in valume. She has been the recipient of desired Jnanpeetha Award for writing in Bengali. She is a productive essayist with imaginative author's inclination to voiceout different socio, social, policy centered issues and subjects with a passionate lobbyist's enthusiasm and relentless government assistance theme of individualscharacters. Mahashweta Devi stands separated as a recognized author.